PENDIDIKAN BUDI PEKERTI DALAM SASTRA: MENYIBAK BUDAYA TATA KRAMA DALAM NOVEL-NOVEL ETNOGRAFIS - DIDIPU, HERMAN (Universitas Negeri Surabaya, 2018)
The purpose of this study is to describe the culture of manners in ethnographic novels. A qualitative descriptive method was employed in this study, and the data were from three ethnographic novels, including Namaku Teweraut by Ani Sekarningsih (2000), Manusia Langit by J.A. Sonjaya (2010), and Cinta Putih di Bumi Papua by Dzikry El Han (2014). The data were collected from close reading and noting techniques, and were further analyzed by using Miles and Huberman qualitative data analysis; data reduction, data display, and conclusions. The result indicates that the culture of manners contained in ethnographic novels include respecting parents, respecting traditional authorities? decision, respecting visitors, greeting and introducing self, and speech ethics.